Do changes in divorce legislation have an impact on divorce rates? The case of unilateral divorce in Mexico - Edith Aguirre (Latin American Economic Review, 2019)
In 2008, Mexico City was the first entity to approve unilateral divorce in Mexico. Since then, 17 states out of 31 have also moved to eliminate fault-based divorce. In this paper, I investigate the effect of the changes in unilateral legislation on divorce rates in Mexico, given the remarkable growth of divorce rates over the past few decades in the country, but especially after the introduction of unilateral divorce. Following a difference-in-differences methodology, two models are developed using panel state-level data. The results indicate that divorce on no grounds accounts for a 26.4% increase in the total number of divorces in the adopting states during the period 2009-2015. Moreover, since no-fault divorce has been implemented gradually in the country, the rising trend in divorce rates is expected to continue over the coming years. Unilateral legislation has proved to be an effective tool in modifying family structures in Mexico, so it is important to be aware of the short- and medium-term consequences of the shift toward divorce on no grounds, in order to improve the delivery of these policies in the country. This is especially important at this point in time, when 14 remaining states may potentially adopt unilateral legislation. This paper is the first one to address the effect of adopting unilateral divorce in the context of a Latin American country.
Keywords: C29; J12; J18; 330; Divorce rates; Unilateral divorce; Diference-in-diferences; Mexico